Menumbuhkan Kesadaran Kewarganegaraan di Kalangan Anak-Anak SD: Implementasi Program Edukids - Muh. Khaerul Ummah BK; Syaiful Hidayat; Hamna; Karmila Risa Rahmawati; Ni’mah Wahyuni; Mustakim; Anggraini Insiano, Dewi (University of Muhammadiyah Malang, 2024)
Growing civic awareness is important because it incorporates the practice of Pancasila values, which are the foundation of life, nation and state. It needs to be done from an early age, starting from basic education to become the next generation and future leadership relay holders. The main aim of this research is to increase children's citizenship awareness at the elementary school level through teaching activities designed through the Edukids Program with a civic perspective, such as unity, diversity and participation in social life. This research method is descriptive qualitative, which is used to describe and analyze with an argumentative-contextualistic approach regarding the implementation of the